2018
DOI: 10.1051/radiopro/2018009
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose from18F-FDG PET/CT procedures: influence of specific CT model and protocols

Abstract: The increasing use of the integrated 18F-fluoro-deoxy-glucose (FDG) positron emission tomography/computed tomography (PET/CT) imaging modality in the management of tubercular lesions raises concerns about associated radiation exposure. This work aimed to study the effects of CT model and study protocols on the overall radiation dose from a PET/CT examination. Two PET/CT systems with five representative CT exposure protocols applied for clinical patients in PET/CT imaging following retrospective evaluation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The CT component contribution to the total dose was between 32% and 77% for GE, and 35% and 79% for Philips. [ 16 ] Huang et al . [ 17 ] reported that the fetal dose from 328 MBq 18 F-FDG was 6.25 mSv, and Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…The CT component contribution to the total dose was between 32% and 77% for GE, and 35% and 79% for Philips. [ 16 ] Huang et al . [ 17 ] reported that the fetal dose from 328 MBq 18 F-FDG was 6.25 mSv, and Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Chawla et al [ 74 ] reported in their study that, from 2002 to 2007, effective doses due to PET/CT ranged from 2.7 to 54.2 milliSieverts (mSv) for the CT scanning and from 0.4 to 7.7 mSv for the PET procedure [ 75 ]. Some authors [ 76 79 ] reported that a non-optimized CT scan can contribute up to 80% of the whole radiation burden in paediatric NM exams. In this context, the Image Gently ’s slogan seems more important than ever: “ One size does not fit all ” [ 80 ].…”
Section: Hybrid Imaging and Ct Dose Optimizationmentioning
confidence: 99%
“…The optimization of CT in hybrid imaging is mainly based on adjusting acquisition parameters [ 82 88 ] as well as reconstruction algorithms [ 89 , 90 ]. Imaging tests and subsequent standardization of the most common protocols used in the department can help reduce patient exposure [ 76 , 91 ] and quantify any bias that may be introduced using a very low dose CT for attenuation correction [ 92 , 93 ].…”
Section: Hybrid Imaging and Ct Dose Optimizationmentioning
confidence: 99%
“…Advanced image reconstruction methods 13–15 and improved detectors have contributed to PET/CT images of much higher spatial resolution and signal‐to‐noise ratio even at substantially lower injected radiotracer dosages. In addition, new CT hardware and software has been proposed to minimize radiation exposure due to the CT component 1,16–18 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, new CT hardware and software has been proposed to minimize radiation exposure due to the CT component. 1,[16][17][18] Previous studies reported that CT contributes to over 50% of the estimated average radiation exposure in 18 F-fluorodeoxyglucose ([ 18 F]FDG) PET/CT examinations-depending on the application. 16,17,19 In South Korea, a nationwide survey was conducted involving all institutions operating PET/CT scanners to evaluate the patient's effective dose for different diagnostic PET/CT procedures performed with various PET tracers.…”
Section: Introductionmentioning
confidence: 99%